Wild desires and mistaken identities : lesbianism and psychoanalysis - O'Connor, Noreen, 1946- (Karnac, 1993)
This groundbreaking book provides a challenging exploration of psychoanalytic ideas about lesbians and lesbianism. Based on the authors' clinical experience as psychoanalytic psychotherapists, it offers a new and thoughtful framework that does not inevitably pathologise or universalise all lesbiansim. A wide range of psychoanalytic ideas are surveyed, from Freud, Deutsch and Jung to Lacan and contemporary object-relations theorists.